Toxicological evaluation of water-extract sericin from silkworm (Bombyx mori) in pregnant rats and their fetus during pregnancy - Jinyue Li; Pingjing Wen; Pingjing Wen; Guangqiu Qin; Guangqiu Qin; Jiehong Zhang; Peng Zhao; Yixin Ye (Frontiers Media S.A., 2022)
Sericin is a natural protein produced by the silkworm Bombyx mori, which has a wide range of biological activities and has a broad application prospect in multiple areas. However, systemic toxicity and safety assessment of sericin is still rare. This study was aimed to evaluate the toxic effects of water-extract sericin from cocoons of Bombyx mori in pregnant rats and their fetuses during pregnancy. Eighty pregnant rats were randomly divided into three treatment groups, one negative and one positive control group. The treatment groups were administered water-extract sericin solutions at doses of 1,000, 500, and 250 mg/kg, while the negative and positive control groups were administered pure water and 300 mg/kg aspirin, respectively. Rats were exposed daily by oral gavage from the seventh day of gestation for 10 consecutive days and sacrificed on the 20th day of gestation. The results showed that water-extract sericin did not induce any treatment-related changes on pregnant rats (clinical signs, body weights, food consumption, ovarian and uterine weights) and fetuses (body weights, body lengths, tail lengths, visceral, and skeletal development). The no-observed-adverse-effect-level (NOAEL) of sericin was determined to be 1,000 mg/kg body weight in rats. These results indicated that water-extract sericin is of low teratogenic potential under the experimental conditions of this study.